Implementation of the Healthy City Program from the Perspective of Health Information Literacy and Community Empowerment - Niken Lastiti Veri Anggaini; Farida Nurani; Wike Wike; Noppawan Phuengpha (Yayasan Keluarga Guru Mandiri, 2026)
This study aims to determine the level of collaboration and literacy, and the extent of community participation, in supporting the realization of a Healthy City. This study used a mixed-methods approach. The respondents in the study were residents of Batu City, East Java Province, Indonesia, grouped by sub-district and level of education. The research sample consists of 150 people, selected using stratified random sampling. Data mining used questionnaires, focus group discussions, observations, and documentation. Data analysis used statistical and interactive modeling, including data collection, condensation, data presentation, and conclusions. This article highlights that access to health information in Batu City is relatively good, but the evaluation and use of information still need improvement. The results also show that community participation is strong in implementation, but weak in planning, monitoring, and evaluation. The average literacy level and community participation in the Healthy City program remain in the medium range. Efforts are needed to educate, advocate, instill noble values, and improve Joint Movement's ability to realize and succeed in the Healthy City Program.